CHATGPT: ATTITUDES AND EXPERIENCES OF TECHNICAL UNIVERSITY STUDENTS IN UKRAINE - Oksana Chugai; Kateryna Havrylenko (Інформаційні технології і засоби навчання)
Given the rising prevalence of AI tools within educational contexts, it is crucial to understand the dynamics of interacting with these technologies, their benefits and drawbacks. This study explores the attitudes and experiences of students at a technical university in Ukraine who utilize ChatGPT. Employing a mixed-method research design, a comprehensive array of quantitative and qualitative data was collected through Google Form surveys from a cohort of 208 student volunteers, ensuring anonymity and voluntary participation. Analysis of the data revealed that the majority of students employed ChatGPT sporadically, primarily seeking assistance with programming tasks and grappling with complex concepts. While students expressed moderate satisfaction with ChatGPT’s support and its perceived enhancement of their grasp of course material, they also acknowledged its positive impact on their academic performance both in technical sciences and humanities. Despite its user-friendly interface, students identified several challenges and limitations, including ChatGPT’s inability to address technical issues and its occasional dissemination of inaccurate or outdated information, necessitating verification. Nevertheless, students displayed a clear inclination toward recommending ChatGPT for academic use to their peers. Their recommendations underscored the importance of cultivating responsible and effective utilization of ChatGPT, refining the construction of prompts, devising strategies to navigate its limitations, and leveraging its educational potential. Statistical analysis, specifically the calculation of median (Mdn) and Inter-Quartile Range (IQR), revealed a consensus regarding ChatGPT’s positive impact on academic performance and its suitability for peer recommendation. This research makes a substantial contribution to the current discussion on incorporating AI into education as educators gain insights that can shape a more informed approach to its integration into teaching. The study highlights the importance of developing strong policy frameworks to guide the ethical and responsible application of AI tools. Further investigations of university instructors’ perceptions and encounters with ChatGPT may be contrasted with those presented in this study. Such a comparative analysis will enable educators to leverage ChatGPT in teaching while upholding academic integrity.